2018
DOI: 10.1053/j.jvca.2017.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Determinations of Oxygen Delivery and Consumption in Cardiac Surgery: An Observational Study

Abstract: Agreement between minimally invasive and invasive DO and VO determinations is, moderate and poor, respectively. These findings may be explained by the poor agreement between minimally invasive and invasive cardiac output measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…(51-53) During stable intraoperative conditions, oxygen content difference is not expected to vary to a large extent whereas cardiac output can show considerable in- and between patient variability. (23) In our study, oxygen content difference and cardiac output demonstrated similar coefficients of variation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…(51-53) During stable intraoperative conditions, oxygen content difference is not expected to vary to a large extent whereas cardiac output can show considerable in- and between patient variability. (23) In our study, oxygen content difference and cardiac output demonstrated similar coefficients of variation.…”
Section: Discussionsupporting
confidence: 79%
“…Newer studies using non-invasive cardiac output monitors have not shown agreement with oxygen consumption measurements from indirect calorimetry(22) or pulmonary artery catheters. (23) However, the monitors used were not calibrated by transpulmonary or indicator dilution such as the PiCCO™ or LiDCO™plus systems and did not analyse changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the earlier method comparison studies are summarised in Table 1 . Newer studies using non-invasive cardiac output monitors have not shown agreement with oxygen consumption measurements from indirect calorimetry [ 20 ] or pulmonary artery catheters [ 21 ]. However, the monitors used were not calibrated by transpulmonary or indicator dilution such as the PiCCO ™ or LiDCO ™ plus systems and did not analyse changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Central and mixed venous oxygen saturation have not shown interchangeability [ 46 48 ] but some studies have suggested that trends in ScvO 2 can replace SvO 2 [ 49 51 ]. During stable intraoperative conditions, oxygen content difference is not expected to vary to a large extent whereas cardiac output can show considerable in- and between patient variability [ 21 ]. In our study, oxygen content difference and cardiac output demonstrated similar coefficients of variation.…”
Section: Discussionmentioning
confidence: 99%
“…If severe peripheral vascular disease is present at both femoral artery and axillary artery, central cannulation could be performed as an alternative. 25,26 Fortunately, we did not transfer the cannulation site to the axillary artery or aorta till now, the shifting of femoral arterial cannulation from right side to left side in only one case from Group B. Importantly, a highly experienced anesthetist and perfusionist is crucially necessary in teamwork in order to well control the heart rate, myocardial contractility, arterial perfusion, and venous drainage during the CPB.…”
Section: Discussionmentioning
confidence: 99%